Organizational behavior : a management challenge - Northcraft, Gregory B.; Neale, Margaret A. (Chicago : Dryden Press, 1990)
The explicit focus of this book is making wisdom and insights of organizational behavior research not just available but accessible-easy to learn-for students.
Introduction -- Individual behavior -- Behavior in groups -- Managing for performance -- The larger context of organizational behavior
Includes index.
Keywords: ORGANIZATIONAL BEHAVIOR; MANAGEMENT